Second Five Year Plan Progress Report 1956-61 Rajasthan - Planning Commission (Planning Commission, 1956)
The completion of the country’s Second Five Year Plan in March, 1961 has marked a concrete step forward towards the national goal of increase in employment, out-put and incomes and improvement in the living standards of the people in general. the process of planned development in a high population-low-income country, necessarily combines forces which tend both to accelerate and retard the pace of economic progress, resulting in creating a gap between the potential and the actual rate of progress achieved in a given period. But for this inescapable draw-back the progress achieved by the planned development would be much higher than what is actually recorded. the success achieved under the Second Plan has to be reviewed against this background of planned development in the country.
Directorate of Economics and Statistics, Rajasthan